The C-Terminal Transmembrane Domain of Cowpea Mild Mottle Virus TGBp2 Is Critical for Plasmodesmata Localization and for Its Interaction With TGBp1 and TGBp3 - Jiang, Chong; Shan, Shiqi; Huang, Yue; Mao, Chenyang; Zhang, Hehong; Li, Yanjun; Chen, Jianping; Wei, Zhongyan; Sun, Zongtao (Frontiers in Microbiology, 2022)
The movement of some plant RNA viruses is mediated by triple gene block (TGB) proteins, which cooperate to transfer the viral genome from cell to cell through plasmodesmata. Here, we investigated the function of the TGB proteins of cowpea mild mottle virus (CPMMV; genus Carlavirus, family Betaflexiviridae), which causes severe damage to soybean production. Subcellular localization experiments demonstrated that TGBp1 and TGBp3 were localized to the endoplasmic reticulum (ER), plasmodesmata (PD) and nucleus in N. benthamiana leaves. TGBp2 was unusually localized to PD. In protein interaction assays TGBp2 significantly enhanced the interaction between TGBp3 and TGBp1. Interaction assays using deletion mutants showed that the C-terminal transmembrane (TM) domain of TGBp2 is critical for its localization to PD and for its interaction with TGBp1 and TGBp3.